نوعيّة الحياة عند مرضى البهاق وعلاقتها بالمتغيّرات المتنوّعة - الخير عبد الله; بلبل ندى (Latakia University Journal -Medical Sciences Series, 2018)
أجريت هذه الدّراسة لتقييم نوعيّة الحياة عند مرضى البهاق وعلاقتها بالمتغيّرات المختلفة. شملت الدّراسة 73 مريض بهاق, تمّ وضع التّشخيص بناءً على العلامات السّريريّة. خُصِص لكل مريض استمارة خاصّة ضمّت المعلومات الدّيموغرافيّة واستبيان VitiQoL, وتمّ حساب مجموع VitiQoL من خلال جمع النّقاط, والمجموع الأعلى يعبّر عن نوعيّة الحياة الأقل. أوضحت دراستنا أنّ نوعيّة الحياة كانت أسوأ عند النّساء منه عند الرّجال, فكل ما يخص الأمور الجماليّة تهم النّساء, كما وُجِدَت علاقة ارتباط مهمّة بين مدّة المرض (15-20) سنة وبين نوعيّة الحياة, حيث أنّ هذه المدّة أثّرت بشكل سلبي على نوعيّة حياة المرضى, وفيما يخص مساحة سطح الجسم المصاب, فقد أظهرت دراستنا وجود علاقة ارتباط طرديّة, أي أنّه بزيادة مساحة سطح الجسم المصاب تنخفض نوعيّة الحياة, وبالنّسبة لمكان توضّع الإصابة فقد أبدى المرضى ذوو الإصابة التّناسليّة نوعيّة حياة أقل, في حين لم نجد في دراستنا أيّة علاقة بين نمط المرض, الحالة الاجتماعيّة, عمر المريض, المستوى التعليمي والنّمط اللوني وبين نوعيّة الحياة. This study was conducted to assess patient life quality and its correlation with various variables. Our survey included 73 vitiligo patients. Diagnosis was established based upon clinical signs. Each patient was assigned a special form, which included demographic information and VitiQol questionnaire, and VitiQol total was calculated via summation of points. The higher total expresses lower quality of life. Our survey has demonstrated that quality of life in women had been worse than that in men, since all that is related to esthetic matters concerns women. An important correlation had been found between duration of disease (15-20) years and quality of life, since this duration negatively affected the patients’ quality of life. With respect to the area of affected body surface, our survey showed a proportional relationship, i.e. the more the affected body surface area, the lower the quality of life, as for the site of disease, the patient with genital involvement have lower quality of life, whereas our survey found no correlation among disease type, social status , patient’s age , educational standard, color pattern, and quality of life.